Evaluation Of Pregnant Women's Satisfaction Towards Pregnant Women Classes Implementation - Suyani Suyani; Erni Retna Astuti (Universitas 'Aisyiyah Yogyakarta, 2021)
The population in this study were all pregnant women who participated in pregnant women classes implementation at public health center Sanden, Bantul Regency, with a total sample of 32 people who were determined by total sampling. The results showed that the satisfaction of pregnant women in the pregnant women classes implementation at public health center Sanden, Bantul Regency were mostly satisfied as many as 22 people (68.8%). ), The satisfaction of pregnant women with the quality of class service for pregnant women at public health center Sanden, Bantul Regency was mostly satisfied as many as 24 people (75%). %), and pregnant women satisfaction with the class service system for pregnant women at public health center Sanden, Bantul Regency, was mostly satisfied as many as 22 people (68.8%). It’s advisable for health workers to maintain the quality of existing class services for pregnant women and always increase pregnant women knowledge about high-risk pregnancies by providing direct information.